2012
DOI: 10.1371/journal.pone.0044300
|View full text |Cite
|
Sign up to set email alerts
|

Human Endometrial Stromal Stem Cells Differentiate into Megakaryocytes with the Ability to Produce Functional Platelets

Abstract: Human endometrium is a high dynamic tissue that contains endometrial stromal stem cells (hESSCs). The hESSCs have been differentiated into a number of cell lineages. However, differentiation of hESSCs into megakaryocytes (MKs) has not yet been investigated. The aim of this study was to investigate the feasibility of MK generation from hESSCs and subsequent production of functional platelets (PLTs). In our study, hESSCs were cultured from endometrial stromal cells as confirmed by positive stromal cell specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 30 publications
0
20
0
2
Order By: Relevance
“…In bibliography, different populations of endometrial stem cells have been described (Chan et al, 2004) and different names have been used for these cells, such as menstrual bloodderived stromal/mesenchymal cells, or endometrial-derived stromal/mesenchymal stem cells (endMSCs) (Kyurkchiev et al, 2010;Gargett et al, 2016). Additionally, different laboratory procedures have been established for in vitro isolation and expansion (Schüring et al, 2011;Wang et al, 2012;Rossignoli et al, 2013). Nowadays, menstrual blood-derived endMSCs can be easily isolated by a non-invasive method, without any painful procedure and their in vitro expansion can be achieved by simple, and reproducible methods (Sun et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In bibliography, different populations of endometrial stem cells have been described (Chan et al, 2004) and different names have been used for these cells, such as menstrual bloodderived stromal/mesenchymal cells, or endometrial-derived stromal/mesenchymal stem cells (endMSCs) (Kyurkchiev et al, 2010;Gargett et al, 2016). Additionally, different laboratory procedures have been established for in vitro isolation and expansion (Schüring et al, 2011;Wang et al, 2012;Rossignoli et al, 2013). Nowadays, menstrual blood-derived endMSCs can be easily isolated by a non-invasive method, without any painful procedure and their in vitro expansion can be achieved by simple, and reproducible methods (Sun et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal cells are distinct from hematopoietic cells, but Wang et al . and our group have demonstrated that MKs and platelets can be generated from mesenchymal cells such as endometrial stromal cells, subcutaneous adipose tissue cells, and preadipocyte cell lines . Mesenchymal cells constitute an advantageous cell source for manufacturing platelets, because differentiation of these cells into MKs and platelets does not require gene transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the differentiated megakaryocytes were able to release functional platelets that can bind fibrinogen after thrombin stimulation in vitro. Ultrastructural assessment of these platelets showed the expression of alpha granules, and a dense tubular system similar to their endogenous circulating counterparts [77]. Further in vivo studies will help to delineate the functionality of HEDSC derived platelets and their potential clinical utility.…”
Section: Differentiation To Megakaryocyte-like Cellsmentioning
confidence: 92%
“…The vast differentiation potential of HEDSC was further supported by an in vitro study, in which HEDSC were differentiated into megakaryocyte-like cells that are able to produce functional platelets [77]. When cultured in media containing thrombopoietin, up to 30% of the cells expressed megakaryocyte markers CD41a and CD42b.…”
Section: Differentiation To Megakaryocyte-like Cellsmentioning
confidence: 93%